1994
DOI: 10.1017/s0334270000009346
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis from fourth order evolution equation for small but finite amplitude interfacial waves in the presence of a basic current shear

Abstract: A fourth-order nonlinear evolution equation is derived for a wave propagating at the interface of two superposed fluids of infinite depths in the presence of a basic current shear. On the basis of this equation a stability analysis is made for a uniform wave train. Discussions are given for both an air-water interface and a Boussinesq approximation. Significant deviations are noticed from the results obtained from the third-order evolution equation, which is the nonlinear Schrodinger equation. In the Boussines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Another form of current that is of interest has shear in the vertical. That type of current has been discussed by Pullin & Grimshaw (1986) and, for the particular case of Dysthe's (1979) MNLS equation, by Dhar & Das (1994).…”
Section: Resultsmentioning
confidence: 99%
“…Another form of current that is of interest has shear in the vertical. That type of current has been discussed by Pullin & Grimshaw (1986) and, for the particular case of Dysthe's (1979) MNLS equation, by Dhar & Das (1994).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of the fourth order evolution equation, which was first pointed out by Dysthe [8] and later elaborated by Janssen [14] and considered by many authors ([2, [5][6][7]11,13,21]) in studying stability of water waves, two coupled nonlinear evolution equations correct to fourth order in wave steepness are obtained for a surface gravity wave packet in the presence of a thin thermocline. These two coupled equations are reduced to a single equation on the assumption that the space variation of the amplitudes takes place along a line making an arbitrary fixed angle with the direction of propagation of the wave packet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we introduce the asymptotic expansion, This system has the form of the Davey-Stewartson equations [3] describing gravity-capillary wave packets on the surface of homogeneous fluid. On the other hand, the system (4.3a)-(4.3b) with parameters presented in Appendix A follows also from the general equations for quasi-harmonic interfacial waves [6][7][8][9] in the shallow-deep limit of the fluid depths. Note that for arbitrary fluid depths the coupling of mean flow n and amplitude 'I' of the interfacial waves is given by a fourth-order differential equation that is different from the Davey-Stewartson system.…”
Section: Two-dimensional Nonlocal Evolution Equationsmentioning
confidence: 99%
“…For the last 30 years the problem of self-modulation of small-amplitude nonlinear waves has been investigated intensively both for surface water waves [1][2][3][4] and for internal waves in a density-stratified fluid [5][6][7][8][9]. It was shown that the cubic nonlinear Schrodinger (NLS) equation is a universal model for a description of wave propagation when there is no resonance between the main quasi-harmonic wave and the second or zero (mean flow) harmonics induced by nonlinear effects.…”
Section: Introductionmentioning
confidence: 99%